RANCANGAN PENGGUNAAN JARINGAN KABEL LISTRIK SEBAGAI MEDIA KOMUNIKASI DATA INTERNET DI POLITEKNIK PENERBANGAN SURABAYA - Atala Hunaifi Achmad; Bambang Bagus Harianto; Yuyun Suprapto (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Currently, the provision of internet network services are still using UTP cables to connect to Wifi / Modems to routers in different areas of the room. If an internet connection is needed in a different room, you must add an UTP cable connected to the switch to get internet access. In development of research and network technology, the Power Line Communication (PLC) test can be use on the design of the use of electric cable media for internet data network transmission using Power Line Communication (PLC). This research will facilitate in accessing internet networks that do not use UTP cables to connect between computers or routers in different rooms. Power Line Communication (PLC) media are using low voltage power lines. Basically, Power Line Communication (PLC) can replace the role of UTP cables in transmitting internet data communications. In terms of network installation, it is much easier than using UTP cables.